Cross-Process Interference in Single-Cycle Electron Emission from Metal Needle Tips - Herzig, Anne; Hommelhoff, Peter; Goulielmakis, Eleftherios; Fennel, Thomas; Seiffert, Lennart (Physical Review Letters, 2026)
Though interference from different emission channels enabled a deeper understanding of strong-field photoemission in atoms and molecules, it remained out of reach for solids. Here, we explore metal needle tips under single-cycle pulses via classical trajectories extended by quantum interference and numerical solution of the time-dependent Schrödinger equation. We find interference of direct and backscattered electrons with fringe pattern encoding subcycle information on birth times and near-field driven acceleration dynamics, opening routes for ultrafast solid-state metrology.
CRIS-Team Scopus Importer:2026-02-20